Altered white matter structure in the visual system following early monocular enucleation. Issue 1 (30th September 2017) - Wong, Nikita A.; Rafique, Sara A.; Kelly, Krista R.; Moro, Stefania S.; Gallie, Brenda L.; Steeves, Jennifer K. E.
Abstract: Partial visual deprivation from early monocular enucleation (the surgical removal of one eye within the first few years of life) results in a number of long‐term morphological adaptations in adult cortical and subcortical visual, auditory, and multisensory brain regions. In this study, we investigated whether early monocular enucleation also results in the altered development of white matter structure. Diffusion tensor imaging and probabilistic tractography were performed to assess potential differences in visual system white matter in adult participants who had undergone early monocular enucleation compared to binocularly intact controls. To examine the microstructural properties of these tracts, mean diffusion parameters including fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were extracted bilaterally. Asymmetries opposite to those observed in controls were found for FA, MD, and RD in the optic radiations, the projections from primary visual cortex (V1) to the lateral geniculate nucleus (LGN), and the interhemispheric V1 projections of early monocular enucleation participants. Early monocular enucleation was also associated with significantly lower FA bidirectionally in the interhemispheric V1 projections. These differences were consistently greater for the tracts contralateral to the enucleated eye, and are consistent with the asymmetric LGN volumes and optic tract diameters previously demonstrated in this group of participants. Overall, these results indicate that early monocular enucleation has long‐term effects on white matter structure in the visual pathway that results in reduced fiber organization in tracts contralateral to the enucleated eye. Hum Brain Mapp 39:133–144, 2018 . ©2017 Wiley Periodicals, Inc.